Mesenchymal stromal cells for the treatment of osteoarthritis of knee joint: context and perspective - Gupta, Pawan Kumar; Thej, Charan (Annals of Translational Medicine, 2019)
Evidence from completed preclinical and clinical studies conducted worldwide suggests that mesenchymal stromal cells (MSCs) are a novel and promising option for the treatment of osteoarthritis (OA). However, ideal tissue sources, route of administration, dose of the cells, single or repeated injection of MSCs to achieve the desired therapeutic efficacy in a disease with complex pathophysiology such as OA are yet to be confirmed.